The Impact of Strategic Thinking on Organisational Performance: A Case Study of Uchumi Supermarket Limited - Juma, Gerald; Minja, Prof. David; Mageto, Joash (International Journal of Supply Chain Management, 2016)
The purpose of this study was to determine how strategic thinking impacts on organizational performance. The researchers used a case study and descriptive research design. The study was guided by Cognitive Hierary Theory and Hybrid EWA Model. The population for this study included all the 1,073 employees at Uchumi Supermarket Kenya Limited based in Kenya. The target population was 116 management staff. A sample of 64 managers from Nairobi County was selected for inclusion in the study. Primary data was collected using self-administered questionnaires and in-depth interview conducted on a senior manager. The data was processed through excel application and Statistical Package for Social Sciences (SPSS). The study found out that successful strategic planning and implementation requires intimate and enthusiastic involvement of all members of the organization and that management teams should strengthen the process of strategic thinking for it to be truly effective. The study recommends that top corporate executives should ensure that there is inclusion of all stakeholders especially employees in the planning process as this greatly encourages psychological attachment, strategic thinking and improves job satisfaction.